Paku Epifit pada Gymnospermae di Kebun Raya Cibodas: Epiphytic Ferns on Gymnosperms at Cibodas Botanical Garde - Adhatirana, Rizkia; Ratna Djuita, Nina; Sulistijorini, Sulistijorini; Nasution, Taufikurrahman (Jurnal Sumberdaya Hayati, 2021)
Epiphytic ferns can be found in host trees from the Angiosperm and Gymnosperm groups. Epiphytic ferns in Angiosperm plants host have been widely studied, but there is little known for Gymnosperm plants host. The aim of this study was to identify the species of epiphytic ferns in the Gymnosperm plants host at Cibodas Botanical Garden and to analyze the diversity of epiphytic ferns based on microclimate conditions and the surface texture of Gymnosperms plants host. Epiphytic ferns diversity data was obtained using purposive random sampling method. Factors that influence the occupancy of ferns are analyzed using Principal Component Analysis. Epiphytic ferns in Gymnosperm host at Cibodas Botanical Garden were identified as 18 species including 7 family. The most dominant species of epiphytic fern is Davallia denticulata (59.45%). Diversity of epiphytic fern on Gymnosperm at Cibodas Botanical Garden is moderate (H’ = 1.81).